A multifaceted approach to prevention of delirium on intensive care. Issue 1 (11th September 2015) - Hanison, James; Conway, Daniel
Abstract: Delirium is a frequent complication of critical illness with an increased risk of death which is difficult to treat effectively. We describe a seven year quality improvement programme that aimed to reduce rates of delirium on intensive care (ICU). We completed two PDSA programmes with a number of changes including alterations to sedation practice and environmental changes to the ICU itself. Rates of delirium reduced from 70% to 44% after the first cycle of change. Rates of delirium were further reduced to 29% after the second cycle of change. The rates are now lower than predicted by the validated prediction tool PRE-DELIRIC. This project demonstrates that a multifaceted approach to prevention of delirium on ICU can deliver sustained reductions in rates of delirium. The impact of the second cycle of change was less than the first, suggesting that further reductions may prove more challenging.